Properties and bioavailability of particulate and mineral-associated organic matter in Arctic permafrost soils, Lower Kolyma Region, Russia - Gentsch, Norman; Mikutta, Robert; Shibistova, Olga; Wild, Birgit; Schnecker, Jörg; Richter, Andreas; Urich, Tim; Gittel, Antje; Santruckova, Hana; Barta, Jiri; Lashchinskiy, Nikolay; Mueller, Carsten W.; et al. (European Journal of Soil Science, 2015)
Permafrost degradation may cause strong feedbacks of arctic ecosystems to global warming, but this will depend on if, and to what extent, organic matter (OM) is protected against biodegradation by mechanisms other than freezing and anoxia. Here, we report on the amount, chemical composition and bioavailability of particulate (POM) and mineral-associated OM (MOM) in permafrost soils of the East Siberian Arctic. The average total organic carbon (OC) stock across all soils was 24.0±6.7 kgm-2 within 100 cm soil depth. Density fractionation (density cut-off 1.6 g cm-3) revealed that 54±16% of the total soil OC and 64±18% of OC in subsoil horizons was bound to minerals. As well as sorption of OM to clay-sized minerals (R2 =0.80; P<0.01), co-precipitation of OM with hydrolyzable metals may also transfer carbon into the mineral-bound fraction. Carbon:nitrogen ratios, stable carbon and nitrogen isotopes, 13C-NMR and X-ray photoelectron spectroscopy showed that OM is transformed in permafrost soils, which is a prerequisite for the formation of mineral-organic associations. Mineral-associated OM in deeper soil was enriched in 13C and 15N, and had narrow C:N and large alkyl C:(O-/N-alkyl C) ratios, indicating an advanced stage of decomposition. Despite being up to several thousands of years old,when incubated under favourable conditions (60%water-holding capacity, 15°C, adequate nutrients, 90 days), only 1.5–5% of the mineral-associated OC was released as CO2. In the topsoils, POM had the largest mineralization but was even less bioavailable than the MOM in subsoil horizons. Our results suggest that the formation of mineral-organic associations acts as an important additional factor in the stabilization of OM in permafrost soils. Although the majority of MOM was not prone to decomposition under favourable conditions, mineral-organic associations host a readily accessible carbon fraction, which may actively participate in ecosystem carbon exchange.